Passively Q-switched fiber laser utilizing molybdenum titanium aluminum carbide (Mo2Ti2AlC2) for pulsed laser generation - Ab Rahman, Mohd Fauzi; Mohd Nasir, Amal Muaz; Anuar, Shairazi Akmal; Abdul Latiff, Anas; Ahmad Razif, Muhammad (Elsevier GmbH, 2023)
In this work, Molybdenum Titanium Aluminum Carbide (Mo2Ti2AlC2) was examined to function as a reliable saturable absorber (SA) for stable pulse generation in the 1563 nm wavelength. To create the Mo2Ti2AlC2-PVA film, Mo2Ti2AlC2 powder with > 200 nm particle size was dispersed into polyvinyl alcohol (PVA) and dried to form a film. The Mo2Ti2AlC2-PVA film had a linear absorption coefficient of about 1.5 dB at the Q-switched working wavelength. The Mo2Ti2AlC2- PVA film was sandwiched between fiber ferules and analyzed in the Erbium-Doped Fiber (EDF) ring cavity design. Self-started Q-switching was realized with pump power ranging from 20 mW to 55 mW. The pulse width shrunk from 21.7 µs to 8.9 µs while the repetition rate increased from 20.45 kHz to 40.40 kHz. The fundamental frequency had a signal-to-noise ratio (SNR) of 61 dB, implying good stability of the pulsed laser. The highest output power and pulse energies are 1.1 mW and 27.2 nJ, respectively. These results demonstrate that Mo2Ti2AlC2 can be a good alter native passive SA to produce laser pulsing in the 1.55-micron wavelength.